Long Pentraxin PTX 3 and Faecal Calprotectin as a Non Invasive Biomarkers for Ulcerative Colitis - Sherif Ezzat; Amal Selim; Mohamed Abd El-Raouf Tawfi k (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Background and Study Aims: as there is no single golden rule for the diagnosis and activity of ulcerative colitis disease, this study is going to discuss the clinical relevance of calprotectin and PTX 3 in cases of ulcerative colitis and their roles as non-invasive methods to diagnose UC and determine disease activity. Patients and Methods: Patients were classifi ed into two groups; group 1 include 40 patients of different phases of activity of UC. Group 2 included 20 healthy volunteers as a Controls. Measurement of feacal calprotectin by using the ELISA (enzyme-linked immunosorbent assay) kit. Measurement of serum Pentraxin3 (PTX 3) by enzyme-linked immunosorbent assay (ELISA). Results: PTX 3 levels were signifi cantly different between mild, moderate and sever patients with  Cwhich the same as calprotectin level. Moreover, PTX 3 was signifi cantly increased more than calprotectin in mild and severe UC patients. Conclusions: PTX 3 is directly produced from the infl amed gut in UC. Plasma PTX 3 concentration is thought to be a useful marker for understanding the disease activity in patients with UC. PTX 3 was found to be more sensitive and specifi c than faecal calprotectin as a marker for infl ammation and disease activity in UC.